APICA - Association for the promotion of African Community Initiatives - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
APICA (Association pour la Promotion des Initiatives Communautaires Africaines) is an organization that supports home-grown development activities or Local Development Initiatives - LDls. This support is offered through national and international...